Respiratory weakness after mechanical ventilation is associated with one-year mortality - a prospective study. Issue 1 (December 2016) - Medrinal, Clément; Prieur, Guillaume; Frenoy, Éric; Robledo Quesada, Aurora; Poncet, Antoine; Bonnevie, Tristan; Gravier, Francis-Edouard; Lamia, Bouchra; Contal, Olivier
Abstract Background Diaphragm dysfunction in mechanically ventilated patients is associated with poor outcome. Maximal inspiratory pressure (MIP) can be used to evaluate inspiratory muscle function. However, it is unclear whether respiratory weakness is independently associated with long-term mortality. The aim of this study was to determine if low MIP is independently associated with one-year mortality. Methods We conducted a prospective observational cohort study in an 18-bed ICU. Adults requiring at least 24 hours of mechanical ventilation with scheduled extubation and no evidence of pre-existing muscle weakness underwent MIP evaluation just before extubation. Patients were divided into two groups: low MIP (MIP ≤30 cmH2 O) and high MIP (MIP >30 cmH2 O). Mortality was recorded for one year after extubation. For the survival analysis, the effect of low MIP was assessed using the log-rank test. The independent effect of low MIP on post mechanical ventilation mortality was analyzed using a multivariable Cox regression model. Results One hundred and twenty-four patients underwent MIP evaluation (median age 66 years (25th –75th percentile 56–74), Simplified Acute Physiology Score (SAPS) 2 = 45 (33–57), duration of mechanical ventilation 7 days (4–10)). Fifty-four percent of patients had low MIP. One-year mortality was 31 % (95 % CI 0.21, 0.43) in the low MIP group and 7 % (95 % CI 0.02, 0.16) in the high MIP group. After adjustment for SAPS 2 score, body mass index and duration of mechanical ventilation, low MIP was independently associated with one-year mortality (hazard ratio 4.41, 95 % CI 1.5, 12.9, p  = 0.007). Extubation failure was also associated with low MIP (relative risk 3.0, 95 % CI 1, -9.6;p  = 0.03) but tracheostomy and ICU length of stay were not. Conclusion Low MIP is frequent in patients on mechanical ventilation and is an independent risk factor for long-term mortality in ICU patients requiring mechanical ventilation. MIP is easily evaluated at the patient's bedside. Trial Registration This study was retrospectively registered inwww.clinicaltrials.gov (NCT02363231) in February 2015.